Accountable, Operable Knowledge: Toward Value Representations of Individual Knowledge in Accounting - Anne Krebs (Copenhagen Business School (CBS), 2018)
Concerned with the management and control of the forces that drive the “knowledge economy”— the research question of the thesis is: How can individual knowledge become operable in dispersed, global contexts to support knowledge-based management decisions at a distance? The conceptual part of the thesis proposes generic, global measurement units in The Intangible Currency, (TIC), to represent the values of individual knowledge resources distributed in a webbased system of non-financial accounting, Intellectual Capital Management Control System, (ICMCS). It suggests methods for knowledge accounting on which to manage allocation of individual knowledge in dispersed firms. The thesis is in three parts. The first part, which applies the theory Design Studies Research, (DSR), conceptualizes the artefacts TIC and ICMCS. The second part produces case-based empirical validations of the two artefacts in a global company. The artefacts are technically and socially tested producing 2x2 tests. The development and implementation process of ICMCS is qualitatively tested and socially analyzed by Actor Network Theory, (ANT) and TIC is quantitatively tested by the use of proxies, because individual knowledge and competence is invisible and ICMCS has not been implemented yet. By four hypotheses the calculative properties in TICs are explored to analyze in an ANT perspective whether the calculative devices, containing no price mechanism, is able to keep the non-financial network of accounting together. The 2x2 validations were successful except for the 4th moment of translation, the mobilization, 267 Callon,Michel 1986in the social validation of ICMCS, where the roll-out was stopped by top management decisions. The third part discusses the used methods, the results and their limitations and alleys for further research. Furthermore, it proposes contributions to literature in IC, Accounting, KM and OM by the concept of TICs as generic calculative devices and measurement units for individual knowledge and competence and the ICMCS as the IC system of accounting, which is assumed to coordinate and distribute Human Capital (HC) by means of clicks mirroring managerial decisions about movements (flow) in the capital. The remaining part of the summary is placed in 6 sections as follows; Firstly, the theoretical problem is presented and secondly a discussion of the empirical relevance is conducted. Thirdly, the research design is briefly described and the main results from the empirical testing presented. The summary is finished by references to the main contributions to theory and practice, and by some limitations and possible avenues for further research.
hdl:10398/9645
Keywords: 650